Effects of exercise interventions on hand-eye coordination and fine motor skills in children with developmental coordination disorder: a meta-analysis - Wenying, Shi; Yaoqi, Hou; Shenning, Zhou; Xiangqin, Song (Frontiers in Physiology, 2025)
ObjectiveThis meta-analysis was conducted to examine the efficacy of exercise interventions in improving hand-eye coordination and fine motor skills in children with developmental coordination disorder (DCD), thereby providing evidence-based support for clinical management strategies targeting these domains.MethodsFour electronic databases (PubMed, Web of Science, Cochrane Library, Embase) were systematically searched for relevant literature published from inception until 18 July 2025. Two researchers independently assessed the quality of included studies using the Cochrane risk-of-bias tool. The inclusion criteria include: children (<12 years old) who have been diagnosed with DCD; The intervention measures were any form of physical activity, while the control group received routine care or waiting; Primary outcome measures included the Movement Assessment Battery for Children (M-ABC), the Bruininks-Oseretsky Test of Motor Proficiency, Second Edition (BOT-2), the Beery-Buktenica Developmental Test of Visual-Motor Integration (Beery VMI), and the Test of Motor Impairment (TOMI). Data synthesis and statistical analyses were performed using RevMan 5.4 and Stata 18.0 software.ResultsA total of 14 literature were included in the meta-analysis, all of which were in foreign languages, with a total sample size of 528 cases. The results of the meta-analysis showed that motor intervention could improve hand-eye coordination (SMD = 0.45, 95%CI: 0.16-0.73, P = 0.002) and fine motor skills(SMD = 0.74, 95%CI: 0.3-1.18, P = 0.001) in children with DCD, and the difference in treatment outcomes between the experimental group and the control group was statistically significant (P < 0.05). The results of subgroup analysis showed that moderate to high intensity hand-eye coordination and fine motor skills improved by moderate and large effects respectively (P < 0.01), and both hand-eye coordination and fine motor skills improved by large effects when the total intervention duration was over 720 min (P < 0.05).ConclusionExercise intervention can effectively improve hand-eye coordination and fine motor skills in children with DCD. However, the magnitude of its therapeutic effect may be affected by the intensity of exercise and the total duration of intervention. Through a systematic exercise program, hand-eye coordination and fine motor skills in children with DCD can be better improved.Systematic Review registrationidentifier CRD420251118109.